Pengaruh Implementasi Akuntansi Karbon Terhadap Efisiensi Operasional Dan Kinerja Lingkungan Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia Periode 2020 – 2024 - Hamdana, Hamdana; Okta Piyani, Henny; Edy Susanto, Eko; Rahmaniah, Nur (Jurnal GeoEkonomi, 2026)
The following study aims to analyze and test the effect of carbon accounting implementation and environmental performance on operational efficiency in companies listed on the Indonesian Stock Exchange for the period 2020-2024. The number of data used is 50, which was obtained through a purposive sampling method. In the analysis process, this study applies various techniques, including descriptive statistical tests, normality tests, classical assumption tests consisting of multicollinearity, heteroscedasticity, and autocorrelation tests, and multiple linear regression tests. In addition, model testing was also carried out through F tests and R² tests, and hypothesis testing using t tests. The results of the study indicate that carbon accounting has a significant effect on operational efficiency, environmental performance does not have a significant effect on operational efficiency, and carbon accounting and environmental performance have a significant effect on operational efficiency simultaneously.